Study of the Electromagnetic Interference Generated by Wireless Power Transfer Systems - Baikova, E.N. (2016)
This paper presents a study related with measuring of radio frequency emissions. The purpose is to determine the level of interference generated by wireless power transfer equipment in a specific frequency range, and to compare those levels to the existing standards. The technology of wireless power transfer, especially for electric vehicles batteries charging, is rapidly developing in the recent years. An increasing use of this technology in industrial and consumer electronic products has raised concerns about the possible unfavorable health-effects onto the human being. Another concern is raised from the high intensity fields produced by wireless power transfer systems which will generate highly undesired influence on other electrical and electronic equipment. As a protection against the potential health effects, the governments imposed limits on the occupational and general public exposure to the radio frequencies. These limitations are set out in national and international safety guidelines, standards and regulations. The measurement and evaluation of the human exposure to electromagnetic fields are essential to guarantee occupational and general public safety.